PENGEMBANGAN MODUL INTERAKTIF PADA PEMBELAJARAN GENETIKA UNTUK MENINGKATKAN HASIL BELAJARDAN PEMAHAMAN KONSEP SISWA SMA ISLAM BATU - Riyanto Riyanto (JEMS: Jurnal Edukasi Matematika dan Sains, 2015)
This study uses research and development (Research and Development / R & D) method. Model development of instructional media used is aDevelopment model consisting of ten steps, but in this study only compriseseight steps, namely: potential and problems, information gathering, productdesign, design validation, the revised design, product testing, product revision,and the final product.  Based on the results of the validation interactive module Genetics by matter experts and media experts shows that genetics interactive module is feasible used with a percentage of the average score of 90%. Based on theresults of the validation interactive CD genetics by material experts showedthat the decent used by a score of 96% while the results validator of mediaexperts with regard to the feasibility of an interactive CD genetics show thatdecent used is by a score of 88% and an average rate of eligibility InteractiveCD showed that the decent genetics used is 92%, this indicates that theinteractive CD genetics can be applied in small scale to see the effectiveness ofthe implementation of this genetic interactive CD.  Based on the results of a small-scale trial Genetics interactive module effectively used by students seen from the kognitive learning outcomes reached 85.3% and students' understanding of concepts of 87.2%.Based on the research results, it can be concluded that genetics developed interactive module gets adequate assessment of experts, as well as the effective use of learning by students of class XII, SMA Islam Batu with kognitive learning outcomesreached 85.3% and students' understanding of concepts of 87.2%.